To Believe an Artist - Lidin, Konstantin (project baikal, 2018)
Graffiti as a mass phenomenon emerged on the wave of protest youth movements at the end of the 1960s and has carried aggressive emotions for a long time. Today, graffiti includes the streams bearing a positive emotional charge. Such graffiti is used to change the attitude and behavior of people in many countries. Using the example of the Irkutsk graffiti artist Master Bo (Kartashov), the article shows how the stigma of being a rioter and a vandal hinders the artist from making positive graffiti in Irkutsk.